Fly Like an Eagle: Career Duration in the FIS Ski Jumping World Cup. (December 2016) - Frick, Bernd; Scheel, Friedrich
We investigate the impact of individual performance and competitive pressure on the duration of ski jumpers' careers. We find that the degree of competition in the respective national associations has a statistically significant impact on individual career duration: Poorly performing athletes have a higher survival probability if they cannot be replaced (i.e., if the jumpers with whom they compete for the limited number of slots in their national team perform even worse). Moreover, "superstars"—(former) World Champions—can expect significantly longer careers as their nominations seem to be justified by their past success rather than by their current performance.